2011
DOI: 10.1002/ptr.3397
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Inhibits Oral Carcinoma Cell Migration and Invasion In Vitro

Abstract: Sulforaphane is a predominant isothiocyanate in Brassica oleracea, a family of cruciferous vegetables, and is known to be inversely related to the risk of various types of human carcinomas. Studies using oral carcinoma cell lines are scarce, however, and the role of sulforaphane on oral carcinoma cell metastasis is yet to be determined. In this study, the growth inhibition of oral carcinoma cell lines by sulforaphane was determined using aqueous soluble tetrazolium salts, and the growth of various oral cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Although AZ alone did not affect the invasiveness of H-727 cells, it potentiated the anti-invasive property of SFN. This finding is in agreement with previous reports where SFN inhibited the in vitro migration of oral carcinoma cells by down regulation of MMP-1 and MMP-2 secretion and ovarian cancer cells by increasing apoptotic cell death via an increase in Bak/Bcl-2 ratio and cleavage of procaspase-9 and poly (ADP-ribose)-polymerase (PARP) [57,58]. Since the 5-year survival rate in metastatic bronchial carcinoids is only 20-30% [4], reduction in the invasive carcinoid cell population upon in vivo AZ + SFN treatment indicates its possible advantage in treating metastatic disease.…”
Section: Discussionsupporting
confidence: 93%
“…Although AZ alone did not affect the invasiveness of H-727 cells, it potentiated the anti-invasive property of SFN. This finding is in agreement with previous reports where SFN inhibited the in vitro migration of oral carcinoma cells by down regulation of MMP-1 and MMP-2 secretion and ovarian cancer cells by increasing apoptotic cell death via an increase in Bak/Bcl-2 ratio and cleavage of procaspase-9 and poly (ADP-ribose)-polymerase (PARP) [57,58]. Since the 5-year survival rate in metastatic bronchial carcinoids is only 20-30% [4], reduction in the invasive carcinoid cell population upon in vivo AZ + SFN treatment indicates its possible advantage in treating metastatic disease.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, MMP-2 is highly expressed in glioblastoma and its expression increases with tumor progression at both the mRNA and protein levels [32]. Recent studies showed that SFN inhibited MMP-2 expression in some tumor cell lines [11], [12]. Moreover, our previous studies and others have confirmed that MMP-2 was the downstream effector of ERK1/2 [27], [28], [33], [34].…”
Section: Introductionmentioning
confidence: 75%
“…Recently, the effect of SFN on tumor cell migration and invasion was reported. Studies showed that SFN inhibited migration in prostate cancer, invasion in breast cancer, and inhibited migration and invasion both in human bladder cancer and oral carcinoma [9], [10], [11], [12]. However, the effect of SFN on glioblastoma migration and invasion has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has also shown the involvement of miR200c inhibition and estrogen receptor activation in SFN-mediated prevention of EMT [95]. SFN suppressed migration and invasion of oral carcinoma cells by suppression MMP-2 [92]. In pancreatic cancer, SFN inhibits EMT as well as self-renewal capacity of stem cells by modulation of sonic hedgehog pathway [82].…”
Section: Metastasismentioning
confidence: 93%
“…SFN also inhibited the metastasis of several cancers by suppression of epithelial-to-mesenchymal transition [82,[92][93][94]. Inhibition of EMT was through suppression of SNAIL and ZEB-1 leading to induction of E-cadherin [94].…”
Section: Metastasismentioning
confidence: 99%